Pengaruh Beban Pendingin Terhadap Temperatur Sistem Pendingin Siklus Kompresi Uap Dengan Penambahan Kondensor Dummy Tipe Trombone Coil Sebagai Water Heater - Arya Bhima Satria; Azridjal Aziz (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Hybrid air conditioning machine with condenser dummy used to solve the problem electrical energy waste and global warming, by utilizing condenser waste of heat that is normally wasted to the environment. The addition of condenser dummy in this research is conducted to see the effect of addition of condenser dummy to the cooling load and temperature. The method used in this research are design methods and experimental. Based on test results, during operation of 120 minutes obtained by hot water temperature 64,33 0C and refrigerant temperature 83,2 0C. When done giving more the cooling load in the room, the refrigerant temperature is also increase so that the temperature of the hot water produced is also increase.Keywords : Hybrid Air Conditioning Machine, Condenser Dummy, Cooling Load and Temperature.